The Basic Human Nature of Someone who Brings the Buddha-Dharma into Life - Thu Hang, Nguyen Thi (RA Journal of Applied Research, 2022)
The person who brings Buddhism into the world must have the qualities to learn and practice the Buddha’s Dharma. The material of Buddha’s dharma/ or quality of Buddha’s dharma is to help sentient beings return to live with their inherent awareness or the nature of awareness and Buddha-nature. This awareness and Buddha nature in the Avatamsaka Sutra is called "the wisdom of the Tathagata." The Lotus Sutra (Suddharma-Pundarika Sutra) is "knowledge of the Buddha." In the Shurangama Sutra, it is the true mind. Zen Buddhism calls it "the original face or Buddha-nature." Phenomenologically, dharmas in the world are governed by the law of impermanence: birth, old age, illness, death, birth and death, and samsara, but in essence, the "true face – original face" of the human being hidden behind the birth and death person is a person with whole nature: permanence, happiness, ego, and purity. A person’s abilities when he realizes his enlightenment and Buddha nature are also the core qualities of a person who wants to bring Buddhism into the world to transform his life.